COVID‐19 pandemic and its impact on dental students: A multi‐institutional survey. Issue 7 (27th March 2021) - Klaassen, Hannah; Ashida, Sato; Comnick, Carissa L.; Xie, Xian Jin; Smith, Becky M.; Tabrizi, Maryam; Arsenault, Karin; Capin, Oriana R.; Scully, Allison C.; da Mata, Cristiane; Soto, Annetty P.; Dias Ribeiro, Ana Paula; et al.
Abstract: Purpose/objectives: To investigate dental students' perceptions and concerns regarding the COVID‐19 pandemic, their coping strategies and support resources, and their perceived stress levels. Methods: A customized 19‐item survey and the perceived stress scale (PSS) were applied to undergraduate dental students from the US, Spain, Ireland, Chile, India, and Brazil between April 10 and July 5, 2020. Linear modeling and mediation analysis were used to explore the relationships among demographics, stressors, coping mechanisms, social support, and stress Results: A total of 4475 students responded to the survey. The majority (72.4%) were women, and 52.3% had no COVID‐19 training at the time of the survey. The students reported that they had to accommodate to changes in patient care (96.6%) and didactic learning (95.2%) activities, while 88.5% of the respondents indicated at least one of their courses moved online. Transition to online courses went "smoothly with some troubles" for 51.8% of the respondents, and 48.3% perceived the faculty as prepared for the online transition; however, 45.9% reported feeling extremely concerned about the impact of COVID‐19 on their education. The average PSS score was 21.9 of 40 (moderate stress). Multivariate models were built for participants with full data ( n  = 3899). Being male, having completed more dental coursework, and perceiving a smoother transition were associated with lower PSS scores; more concern about academic progress was associated with higher PSS. Faculty support mediated the relationship between a smoothness of transition and concern about academic progress and PSS scores Conclusion: Stress caused by the pandemic may be alleviated by smoother transition and good faculty support.